On the Potential of Blue Hydrogen Production in Colombia: A Fossil Resource-Based Assessment for Low-Emission Hydrogen (2022)
Latin America is starting its energy transition. In Colombia, with its abundant natural resources and fossil fuel reserves, hydrogen (H2) could play a key role. This contribution analyzes the potential of blue H2 production in Colombia as a possible driver of the H2 economy. The study assesses the natural resources available to produce blue H2 in the context of the recently launched National Hydrogen Roadmap. Results indicate that there is great potential for low-emission blue H2 production in Colombia using coal as feedstock. Such potential, besides allowing a more sustainable use of non-renewable resources, would pave the way for green H2 deployment in Colombia. Blue H2 production from coal could range from 700 to 8000 ktH2/year by 2050 under conservative and ambitious scenarios, respectively, which could supply up to 1.5% of the global H2 demand by 2050. However, while feedstock availability is promising for blue H2 production, carbon dioxide (CO2) capture capacities and investment costs could limit this potential in Colombia. Indeed, results of this work indicate that capture capacities of 15 to 180 MtCO2/year (conservative and ambitious scenarios) need to be developed by 2050, and that the required investment for H2 deployment would be above that initially envisioned by the government. Further studies on carbon capture, utilization and storage capacity, implementation of a clear public policy, and a more detailed hydrogen strategy for the inclusion of blue H2 in the energy mix are required for establishing a low-emission H2 economy in the country.